AB0297 Dose reduction in patients with rheumatoid arthritis responding to the standard rituximab regimen. (23rd January 2014) - Batticciotto, A.; Varisco, V.; Antivalle, M.; Talotta, R.; Rigamonti, F.; Ventura, D.; Atzeni, F.; Sarzi-Puttini, P.
Abstract : Background: Rituximab (RTX), a chimeric anti-CD20 monoclonal antibody, safe and effective in rheumatoid arthritis (RA) patients with inadequate response orintolerant to tumor necrosis factor (TNF) inhibitorshas been approved at dose of 1g fortnightlyevery six months. The SERENA and MIRROR studies have shown that response rates are similar in patients treated with 2x0.5g and 2x1g every six months, but there is no agreement concerning the optimal RTX strategy over time (1 .2 ). Objectives: To verify whether RA patientsEULAR responders after the third course of RTX 2x1g achieve the same result after reducing RTX doseto 2x0.5g Methods: Among seventy active RA patients with inadequate response to MTX (range 7.5-20 mg/week) and at least one anti-TNF inhibitor treated in our Center since 2007 we selected twenty-one patients that reached a good-moderate EULAR response after treatment with three courses of RTX 2x1g every six months. At the fourth course they were randomly treated with RTX 2x0.5g (group 1: 10 patients, 9 F, mean age 48 years, range 21-68; mean disease duration 9.7±6.2 years, 5 RF + and 6 anti-CCP +, baseline DAS28: 4.62±0.98) or RTX 2x1g (group 2: 11 patients, 8 F, mean age 61 years, range 39-74; mean disease duration 11.1 ± 8.3 years, 9 RF + and 8 anti-CCP +, baseline DAS28: 4.85±1.35) every six months for 52 weeks Results: No difference between the two groups in disease duration (p=0.832), baseline DAS28 (p=0.647), percentage of patient RF+ (p=0.055) and anti-CCP+ (p=0.126) are observed. The percentage of patients in low disease activity (LDA) or remission based on DAS28 were similar in both groups after the fourth (70.0% vs 72.8% p=1, 0) and fifth course (83.3% vs 66.7% p= 0.545). They maintained the same rate of EULAR response respect baseline (100% vs 90.1% p= 1 after course four and 100% vs 100% after course five). Conclusions: In patients responders to three standard doses of RTX, it is possible to reduce the dose to 2x0, 5g without affecting response and optimizing the pharmacoeconomic impact. Further studies to evaluate the radiological progression of RA after dose reduction are suggested. References: Emery P, et al. Efficacy and safety of different doses and retreatment of rituximab: a randomised, placebo-controlled trial in patients who are biological naive with active rheumatoid arthritis and an inadequate response to methotrexate (SERENE). Ann Rheum Dis. 2010;69:1629-35. Rubbert-Roth A, et al . Efficacy and safety of various repeat treatment dosing regimens of rituximab in patients with active rheumatoid arthritis: results of a Phase III randomized study (MIRROR). Rheumatology ( Oxford ). 2010;49:1683-93. Disclosure of Interest: None Declared